Transforming Growth Factor‐β Pathway: Biological Functions and Therapeutic Targets - Reham Hassan Mekky; Mohammed E. Abo‐El Fetoh; Safaa A. Faheem; Abdullah F. Radwan; Mariam H. Fawzy; Aya M. Mustafa; Mohamed A. Said; Daniela Calina; Javad Sharifi‐Rad; William C. Cho (MedComm)
ABSTRACT Cancer progression is often driven by aberrant cell growth and genetic mutations, leading to metastasis. The transforming growth factor‐beta (TGF‐β) pathway, a key regulator of cellular growth and differentiation, exhibits dual roles in cancer by initially acting as a tumor suppressor and later promoting tumor progression and metastasis. Natural compounds, recognized for their diverse bioactivities and low toxicity, have shown potential in targeting cancer‐related pathways, including TGF‐β signaling. This review examines the therapeutic potential of natural products in modulating TGF‐β signaling and their anticancer effects across various cancer types. We evaluated relevant preclinical and clinical studies assessing the impact of natural products on TGF‐β modulation and cancer progression. Natural compounds from sources such as plants impact TGF‐β signaling, influencing processes like cell proliferation, apoptosis, and angiogenesis. Key compounds reviewed include ginsenosides, halofuginone, and epigallocatechin gallate, demonstrating significant anticancer activity via TGF‐β pathway modulation. These findings suggest natural products may serve as complementary therapies in cancer treatment by targeting TGF‐β signaling, potentially improving patient outcomes. Continued research and clinical evaluation are necessary to integrate these compounds into conventional cancer therapies, aiming to offer safer, cost‐effective options that enhance quality of life.